2010
DOI: 10.1007/s00726-010-0582-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacterial cell factories for gamma-aminobutyric acid

Abstract: Gamma-aminobutyric acid is a non-protein amino acid that is widely present in organisms. Several important physiological functions of gamma-aminobutyric acid have been characterized, such as neurotransmission, induction of hypotension, diuretic effects, and tranquilizer effects. Many microorganisms can produce gamma-aminobutyric acid including bacteria, fungi and yeasts. Among them, gamma-aminobutyric acid-producing lactic acid bacteria have been a focus of research in recent years, because lactic acid bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
245
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(252 citation statements)
references
References 73 publications
3
245
3
1
Order By: Relevance
“…GABA has several well-known physiological functions, including neurotransmission, induction of hypotensivity, a diuretic effect, and tranquilizer effects [12,13]. Although we found that Lb.…”
Section: Introductioncontrasting
confidence: 54%
“…GABA has several well-known physiological functions, including neurotransmission, induction of hypotensivity, a diuretic effect, and tranquilizer effects [12,13]. Although we found that Lb.…”
Section: Introductioncontrasting
confidence: 54%
“…Microbes have evolved the ability to eavesdrop on host neurotransmitter and hormonal conversations and even exploit such host factors to their advantage. Gut bacteria may also interject into the conversation by producing a range of their own neurotransmitters, which mimic those of the host and thus alter neural pathways, such as GABA, norepinephrine (NE), serotonin, and dopamine (al Mardini et al, 1991;Li and Cao, 2010;Barrett et al, 2012;Cryan and Dinan, 2012). This interkingdom communication is extraordinary; however, it may be more parasitic than mutualistic on the part of the bacteria.…”
Section: Potential Mechanism Microbiota Alterations Lead To Asd and Rmentioning
confidence: 99%
“…It functions as the chief inhibitory neurotransmitter for the mammalian central nervous system and is involved in many other physiological processes such as induction of hypotension and diuretic effects. Being a potentially important pharmaceutical chemical and food additive, microbial production of GABA has attracted interest from research and industry (22). Many microbes are able to synthesize and metabolize GABA.…”
mentioning
confidence: 99%